Childhood in social learning models with changing environments: Implications for human evolution. (December 2021) - Holte, Serena J.; Ohmann, Paul R.
Abstract: Childhood is a time of learning, both individually and through social interactions. But the vulnerability inherent in childhood represents a fitness cost: individuals do not have progeny during childhood, and childhood is a net drain of familial or group resources. In this study we model childhood in resource acquisition scenarios where social learning through observation competes with learning through innovation across multiple generations in a variety of environments. In general, observing others allows useful knowledge to be gained more efficiently than self-exploration and may result in significantly greater resource acquisition. However, social learning needing a lengthy childhood to develop advanced cognitive ability may offset the net fitness advantage that might otherwise be gained. Through simulations we demonstrate that individuals with a substantial childhood burden acquire more lifetime resources by observing others than do individuals with negligible childhood costs using self-exploration, as long as the environment is fairly stable. This advantage decreases as the environment becomes less predictable, and reverses in rapidly changing environments where knowledge is unreliable. These results suggest that hominid evolution, with vastly growing cognitive abilities and a longer, more vulnerable childhood, may have been facilitated in similarly stable environments. On the other hand, hominid populations may have been particularly vulnerable to environmental instability. We apply this insight to the Out of Africa Homo sapiens migration roughly 50, 000 years ago and show consistency with the serial founder model that best fits current archeological and genetic evidence. Our findings are important for models of social learning, especially those that describe the emergence and spread of Homo sapiens . Highlights: Childhood is a time of learning but can be a net drain of resources. Childhood can be more significant for strategic fitness than the degree of danger. Social learning needing long childhood is advantageous only in stable environments. Results suggest that hominid evolution is favored in stable environments. Results support serial founder model in Out of Africa human migration 50 kya.